Kinematics of Signature Writing in Healthy Aging1. Issue 4 (19th February 2014) - Caligiuri, Michael P.; Kim, Chi; Landy, Kelly M.
Abstract Forensic document examiners (FDE) called upon to distinguish a genuine from a forged signature of an elderly person are often required to consider the question of age‐related deterioration and whether the available exemplars reliably capture the natural effects of aging of the original writer. An understanding of the statistical relationship between advanced age and handwriting movements can reduce the uncertainty that may exist in an examiner's approach to questioned signatures formed by elderly writers. The primary purpose of this study was to systematically examine age‐related changes in signature kinematics in healthy writers. Forty‐two healthy subjects between the ages of 60–91 years participated in this study. Signatures were recorded using a digitizing tablet, and commercial software was used to examine the temporal and spatial stroke kinematics and pen pressure. Results indicated that vertical stroke duration and dysfluency increased with age, whereas vertical stroke amplitude and velocity decreased with age. Pen pressure decreased with age. We found that a linear model characterized the best‐fit relationship between advanced age and handwriting movement parameters for signature formation. Male writers exhibited stronger age effects than female writers, especially for pen pressure and stroke dysfluency. The present study contributes to an understanding of how advanced age alters signature formation in otherwise healthy adults.